2008
DOI: 10.1007/s00484-007-0143-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of negative air ions on activity of neural substrates involved in autonomic regulation in rats

Abstract: The neural mechanism by which negative air ions (NAI) mediate the regulation of autonomic nervous system activity is still unknown. We examined the effects of NAI on physiological responses, such as blood pressure (BP), heart rate (HR), and heart rate variability (HRV) as well as neuronal activity, in the paraventricular nucleus of the hypothalamus (PVN), locus coeruleus (LC), nucleus ambiguus (NA), and nucleus of the solitary tract (NTS) with c-Fos immunohistochemistry in anesthetized, spontaneously breathing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Three studies of animals exposed to positive and negative air ions for periods of 30 min to 8 weeks reported no modest or consistent effects of exposure on heart rate, respiration rate, or blood pressure [ 106 – 108 ]. The fourth study, Suzuki et al [ 109 ], measured the heart rate and blood pressure responses of anesthetized rats to negative air ions and reported no reliable effects. Suzuki et al [ 109 ], however, also measured levels of c - fos protein, a marker of neuronal activity, in brain regions that receive input from peripheral sensory autonomic nerves.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies of animals exposed to positive and negative air ions for periods of 30 min to 8 weeks reported no modest or consistent effects of exposure on heart rate, respiration rate, or blood pressure [ 106 – 108 ]. The fourth study, Suzuki et al [ 109 ], measured the heart rate and blood pressure responses of anesthetized rats to negative air ions and reported no reliable effects. Suzuki et al [ 109 ], however, also measured levels of c - fos protein, a marker of neuronal activity, in brain regions that receive input from peripheral sensory autonomic nerves.…”
Section: Resultsmentioning
confidence: 99%
“…In a study on rats, negative air ions were also found to modulate the regulation of autonomic nervous system activity and to influence HRV [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…They thought that the measured skin temperature elevation might be the result of the acceleration of percutaneous blood circulation. Niwa et al22 moreover, suggested that far-infrared radiation could induce cellular activation in a variety of tissues by increasing [Ca 2+ ] uptake by the cell membrane, while Suzuki et al27 suggested that negative ions contribute to the inhibition of stress responses via a neural mechanism, involving the modulation of autonomic regulation. Also there are reports that daily treatment with an infrared lamp raised skin temperature, induced improvement in all patients within 3 weeks23.…”
Section: Discussionmentioning
confidence: 99%